2005
DOI: 10.1002/hlca.200590131
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of 1,2,3‐Trisubstituted Guanidines

Abstract: Submitted to honor the 85th birthday of Rolf Huisgen: inspiring chemist and good friend An operationally straightforward and efficient benzotriazole-based method for the guanylation of diverse amines by use of the new reagent classes (bis-benzotriazol-1-yl-methylene)amines 13a ± 13f and benzotriazole-1-carboxamidines 17a ± 17i is described. The preparation is described for a variety of both acyclic and cyclic 1,2,3-trisubstituted guanidines in high yields.Introduction. ± A wide variety of structurally diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Guanidines are of great importance in the pharmaceutical industry due to their many synthetic applications, often being utilized as heterocyclic precursors, strong bases and catalysts, and their alkaloids have exhibited a broad range of antimicrobial and antitumor activities . For these reasons, much effort has gone into the development of facile, efficient guanylating reagents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guanidines are of great importance in the pharmaceutical industry due to their many synthetic applications, often being utilized as heterocyclic precursors, strong bases and catalysts, and their alkaloids have exhibited a broad range of antimicrobial and antitumor activities . For these reasons, much effort has gone into the development of facile, efficient guanylating reagents.…”
Section: Methodsmentioning
confidence: 99%
“…For these reasons, much effort has gone into the development of facile, efficient guanylating reagents. Many methods for the synthesis of substituted guanidines reported in the literature often perform well with electron‐rich amines, but only modestly, if at all, with electron‐deficient aromatic amines . This paper reports a clean, convenient one‐pot synthesis of guanidines from electron‐deficient aromatic amines using chloroformamidine hydrochloride as the guanylating reagent.…”
Section: Methodsmentioning
confidence: 99%
“…8 (F) The Diels-Alder addition of bis(benzotriazole-1-yl)methanethione to cyclopentadiene provides the moisture-stable crystalline adduct. 9 (G) Katritzki et al have reported the synthesis of acyclic and cyclic 1,2,3-trisubstituted guanidines 10 in high yield with a convenient method for the guanylation of various primary and secondary amines by the use of (bisbenzotriazol-1-yl-methylene)amines and benzotriazole-1-carboxamidines. These reagents are prepared by bis(benzotriazole-1-yl)methanethione.…”
Section: Abstractsmentioning
confidence: 99%
“…192 An optimised method for the production and purification of microsystin-LR (75) has been reported, describing conditions for M. aeruginosa PCC7806 growth, extraction, purification in two steps and storage in MeOH. 193 Both microcystin-LR and nodularin (76) are degraded in a similar way by hydrolases of an unidentified bacterial strain B-9, which promote sequential hydrolysis, first at the Arg-Adda junction, then at the Ala-Leu peptide bond and finally at the Adda-Glu connection (Scheme 18). The products and intermediates formed during this degradation process have been identified by LC-ITMS (ion trap mass spectrometry).…”
Section: Natural Guanidines From Marine and Freshwater Microorganismsmentioning
confidence: 99%
“…73,74 Concomitantly, new methods for guanidine synthesis have been reported in the literature. These include new guanylating agents such as N,N 0 ,N 00 -tri-Boc-guanidine, which reacts with amines to give di-Boc-protected guanidines and mono-Boc-protected amidinoureas (Scheme 1), 75 the use of (bis-benzotriazole-1-yl-methylene)amines or benzotriazole-1-carboxamidines for the preparation of 1,2,3-trisubstituted guanidines (Scheme 2), 76 use of hexamethyldisilazane (HMDS) and acylthioureas to prepare acylguanidines, 77 or HMDS as a catalyst in the reaction of disubstituted carbodiimides with aromatic amines to yield di-substituted aromatic guanidines, 78 use of a solvent-free, microwave-assisted, KF-Al 2 O 3 -catalyzed reaction between an acylthiourea and an amine, 79 a one-pot reaction for the preparation of N G -hydroxyguanidines using a primary amine, carboxybenzylisothiocyanate and tetrahydropiranylhydroxylamine (Scheme 3), 80 the use of a vanadium-based catalyst for the guanylation of aromatic amines with carbodiimides (Scheme 4), 81 a remarkable method employing rare-earth (Y, Yb and Lu) alkyl complexes as efficient catalysts within the coupling reaction between carbodiimides and amines to give substituted guanidines (Scheme 5), 82,83 related to a similar procedure using a titanocarborane amide complex (Scheme 6), 84 the preparation of chiral guanidines from chiral homoallyl amines, 85 synthesis of trichloroethoxysulfonyl-protected guanidines and subsequent oxidative cyclisation using a rhodium-based catalyst, 86 as well as rather classical guanidine preparations using either BrCN 87 or substituted thioureas and BiI 3 /NaBiO 3 as catalyst. 88 The use of O-methylisourea for the preparation of homoarginines from lysine residues has proven to be useful in proteomics.…”
Section: Introductionmentioning
confidence: 99%